(untitled) (Communications in Computational Physics, 2018)
In this paper, a new earthquake location method based on the waveform inversion is proposed. As is known to all, the waveform misfit function under the L2 measure is suffering from the cycle skipping problem. This leads to a very small convergence domain of the conventional waveform based earthquake location methods. In present study, by introducing and solving two simple sub-optimization problems, we greatly expand the convergence domain of the waveform based earthquake location method. According to a large number of numerical experiments, the new method expands the range of convergence by several tens of times. This allows us to locate the earthquake accurately even from some relatively bad initial values.